OPTIMASI HYDROXYPROPYL METHYLCELLULOSE DAN CHITOSAN PADA TABLET FLOATING-MUCOADHESIVE SIMETIDIN DENGAN METODE DESAIN FAKTORIAL - Mohammad Zulfikhar A.; Dwi Nurahmanto; Lusia Oktora R.K.S. (Jurnal Ilmiah Manuntung, 2019)
Cimetidine is an H2 receptor antagonist which can be used to reduce acid secretion in the stomach by inhibiting selective binding of histamine to H2 receptors so that it can reduce the concentration of cyclic-adenosine monophosphate (c-AMP) which plays a role in the proton pump mechanism. The combination of floating and mucoadhesive systems is used to increase drug retention in the stomach so that it can reduce the drug interval and increase bioavailability of the drug. The purpose of this study was to make floating-mucoadhesive cimetidine tablets using Hydroxypropyl Methylcellulose (HPMC) as a floating polymer and chitosan as a mucoadhesive polymer. Tablets are expected to have the ability to maintain the dosage form in the stomach for approximately 12 hours. The evaluations carried out included the flow characteristics and the angle repose of the powder mixture, tablet weight uniformity, tablet hardness, tablet friability, floating lag time, floating duration time and tablet mucoadhesive strength. The responses observed were the ability to float and the mucoadhesive strength of tablets. The tablet release test (dissolution) for the optimum formula was performed to determine the character of tablet release. The optimum amount for HPMC is 146,686 mg and chitosan are 50 mg. The combination of polymers with this amount produces a floating lag time of 43,458 seconds, floating duration time >12 hours and the strength of mucoadhesive is 100 grams. The release of the optimum formula in the 720th minute is about 73,180% following the Higuchi release model with dissolution efficiency (DE720) about 67,855%.